Leveraging context-awareness to better support the IoT cloud-edge continuum - Carvalho, Liliana I. (2020)
Novel Internet of Things (IoT) requirements derived from a broader interconnection of heterogeneous devices have pushed the horizons of Cloud computing and are giving rise to a wider decentralisation of applications and data centers. An answer to the underlying network concerns, such as the need to lower the resulting latency due to heavy computation needs, or safety aspects, gave rise to Edge/Fog computing, where IoT functionality can be also supported closer to data sources. While it is today feasible to perform some IoT functionality on the Edge, the orchestration of operations between Edge and Cloud requires an automated support, where context-awareness plays a key role in assisting the network in deciding when and where to store data and to perform computation. This work is focused on the application of context-awareness to support a smoother operation of the Edge to Cloud operation, aiming at lowering latency, in particular when real-time or close-to-real-time data exchange is present.